2007
DOI: 10.1086/520980
|View full text |Cite|
|
Sign up to set email alerts
|

Micafungin versus Caspofungin for Treatment of Candidemia and Other Forms of Invasive Candidiasis

Abstract: Dosages of micafungin 100 mg daily and 150 mg daily were noninferior to a standard dosage of caspofungin for the treatment of candidemia and other forms of invasive candidiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
485
5
24

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 579 publications
(536 citation statements)
references
References 31 publications
22
485
5
24
Order By: Relevance
“…In fact, the clinical significance of paradoxical growth during echinocandin therapy of candidiasis is unproven. In two clinical trials, there were no differences in responses to echinocandins among patients with candidiasis who received high-or low-dose regimens (150 versus 100 mg of micafungin/day and 150 mg/day versus a 70-mg load, followed by 50 mg of caspofungin/day) (4,21). In a mouse model of systemic candidiasis, only one of four C. albicans isolates that demonstrated a paradoxical effect in vitro showed a similar pattern in vivo with a higher fungal burden recovered from mice treated with high-dose caspofungin (20 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the clinical significance of paradoxical growth during echinocandin therapy of candidiasis is unproven. In two clinical trials, there were no differences in responses to echinocandins among patients with candidiasis who received high-or low-dose regimens (150 versus 100 mg of micafungin/day and 150 mg/day versus a 70-mg load, followed by 50 mg of caspofungin/day) (4,21). In a mouse model of systemic candidiasis, only one of four C. albicans isolates that demonstrated a paradoxical effect in vitro showed a similar pattern in vivo with a higher fungal burden recovered from mice treated with high-dose caspofungin (20 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Also voriconazole and caspofungin were shown to be as effective as dAmB but less toxic [22,23]. Subsequently, in two randomized trials, micafungin was shown to be as effective as caspofungin and as liposomal amphotericin B (LAmB) [24,25].…”
Section: Invasive Candidiasismentioning
confidence: 99%
“…It must however be underlined that, beside toxicity, the efficacy between the two drugs showed no significant differences. Pappas et al [25] compared two dosages of micafungin to caspofungin. The results showed that 100 mg daily and 150 mg daily were non-inferior to a standard dosage of caspofungin for the treatment of candidemia.…”
Section: Treatment Of Documented Infectionmentioning
confidence: 99%